Exploring the Effect of Immediate Video Feedback on Coaching. Issue 1 (March 2017) - Suhrheinrich, Jessica; Chan, Janice
Although evidence-based practices for autism spectrum disorders exist, they are often not effectively incorporated into school-based programs, indicating a need for enhanced training strategies for educators. This study examined the effects of immediate video feedback during coaching for teachers and paraprofessionals learning Classroom Pivotal Response Teaching (CPRT). Special education teachers, along with their classroom paraprofessionals, were randomly assigned to a coaching as usual (CAU) or a coaching with video enhancement (VE) condition. Both groups received both verbal and written feedback regarding strengths and weaknesses of their CPRT implementation. Additionally, the VE condition received video feedback during their coaching sessions. Overall, teachers demonstrated higher fidelity of implementation than paraprofessionals, t (44) = −2.73, p < .01, but no significant group differences were identified between VE and CAU conditions. Univariate analysis of variance models were conducted to examine the relationship between participant satisfaction regarding overall quality of the training and highest percentage of CPRT components passed, F (2, 37) = 3.93, p = .03. Results indicate use of the iPad may impact training outcomes and participant satisfaction with training procedures and add to the very limited literature on how technology may be used to enhance in-service training for teachers.